2014
DOI: 10.4028/www.scientific.net/amm.699.552
|View full text |Cite
|
Sign up to set email alerts
|

Production of Biodiesel from Waste Cooking Oil via Ultrasonic-Assisted Catalytic System

Abstract: In this study, production of biodiesel from waste cooking oil (WCO) was carried out via ultrasonic-assisted transesterification method. Calcium oxide (CaO) was used as a catalyst. The effects of methanol to oil molar ratio, reaction temperature and the catalyst amount towards the percentage conversion of oil to biodiesel were investigated. The biodiesel produced was analyzed using GC-FID method. The results obtained showed that 82 % of oil was successfully converted into biodiesel. This indicates that the used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
1
5
1
Order By: Relevance
“…Since the reaction requires 3 moles of methanol for each one mole of triglyceride, high methanol/oil ratio should be required to yield 3 moles of fatty acid alkyl esters and one mole of glycerol (Encinar et al, 2018). In the present study, relatively low methanol/oil ratio (7:1) produced the highest cetane number and bioethanol yield, contradicting Ngadi et al (2015), in which high ratio (15:1) found to generate the highest bioethanol yield. This had to do with the reflux system employed in the study.…”
Section: Discussioncontrasting
confidence: 57%
“…Since the reaction requires 3 moles of methanol for each one mole of triglyceride, high methanol/oil ratio should be required to yield 3 moles of fatty acid alkyl esters and one mole of glycerol (Encinar et al, 2018). In the present study, relatively low methanol/oil ratio (7:1) produced the highest cetane number and bioethanol yield, contradicting Ngadi et al (2015), in which high ratio (15:1) found to generate the highest bioethanol yield. This had to do with the reflux system employed in the study.…”
Section: Discussioncontrasting
confidence: 57%
“…It can be observed that the reaction conversion was enhanced to 73.75% with an increase in catalyst concentration from 1% to 5%. The higher reaction conversion was accomplished on account of the increased number of active sites available for the reaction [ 43 , 44 ]. Thus, it accelerated the reaction to reach the equilibrium.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in temperature will only affect the composition of methanol in oil as the methanol will start to vaporize at its boiling point. Because the transesterification reaction is reversible, the transesterification could be sped up by increasing the amount of methanol [37]. The estimation of the optimum process conditions for these three variables was based on the findings in these three figures.…”
Section: Interaction Effect Of Methanol To Oil Molar Ratio and Reacti...mentioning
confidence: 99%